Effect of dry cow therapy on antimicrobial resistance of mastitis pathogens post-calving - Okello, Emmanuel; ElAshmawy, Wagdy R.; Williams, Deniece R.; Lehenbauer, Terry W.; Aly, Sharif S. (Frontiers in Veterinary Science, 2023)
was adopted to minimum inhibitory concentration measurements to permit interpretation of model exponentiated coefficients. Models for cows with CNS isolated at both S1 and S2 showed increased resistance against cephalothin, oxacillin, and ceftiofur in cows that received DCT from the same drug class, or a class with a shared resistance mechanism. In contrast, resistance of CNS isolates to tetracycline were associated with any AMD therapy at dry off. Resistance of CNS isolates to Penicillin decreased in CNS isolates in cows that received any AMD therapy at dry off compared to those that didn't. The study provided evidence that dry-cow IMM AMD was associated with AMR post-calving.